FAR-INFRARED RAYS' BENEFICIAL EFFECTS ON RATS' FULL-THICKNESS SKIN WOUND HEALING - Farhan Saeed Ali Almalki, Ashwag Assaf Salem Alshehri, Jawhara Abdulaziz Halabi, Rajaa Abdullah Mohmuod, Ahmed Abdullah M Alhazim, Fahad Hassan Mossa Shafie, Ibrahim Ali Ahmed Nahari, Hisham Mohamed Darraj,,; Yahya Mohammed Namis, Abdullah Nasser Alotaibi, Yousef Mohammed Gh Almutairi, Abdulmajeed Awadh Aljaber, (Chelonian Research Foundation, 2022)
It is still unclear how far-infrared radiation (FIR) affects entire organisms biologically. Our study's objectives were to look at the biological impacts of FIR radiation on wound healing in addition to the hyperthermic effect of the radiation. Using a rat model, the rate of full-thickness skin wound healing was compared between groups with and without FIR in order to assess the impact of FIR on a skin wound site. Prior to and during FIR irradiation, we examined the skin's temperature, blood flow, and wound area. We also carried out a histological inspection. With FIR, wound healing occurred noticeably faster than it did without it. Neither before nor during FIR irradiation, there was a discernible change in skin temperature or blood flow. Histological results showed that in wounds from the FIR group, there was more collagen regeneration and infiltration of fibroblasts that expressed transforming growth factor-B1 (TGF-β1). Depending on skin temperature and blood flow, stimulation of TGF-B1 production or fibroblast activation may be one of the potential mechanisms for the beneficial effect of FIR on wound healing. Exp Biol Med 2000; 228:724–729 Key words: collagen, fibroblast, transforming growth factor-61, wound healing, and far-infrared radiation.